How Work Duration, Job Satisfaction, and Life Satisfaction Effect Organizational Citizenship Behavior (OCB) In Taiwan: Case of Indonesian Migrant Worker - Elvina, Yuli; Hsu, Chiehwen Ed; Chang, Yung‐Chi (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
The existing literature indicates that Organizational Citizenship Behavior (OCB) is closely linked to employment and can significantly affect organizational effectiveness, including its adaptability to changing environments and its ability to attract potential talent. This study investigates the potential correlation between job satisfaction, life satisfaction in the workplace, and OCB among Indonesian migrant workers in Taiwan. The study's primary objectives were twofold: to investigate the contributions of job satisfaction and life satisfaction toward fostering Organizational Citizenship Behavior (OCB) within Taiwanese companies, particularly those managing human resources. Furthermore, the research aimed to pinpoint areas for potential enhancement of OCB and better comprehension of the underlying factors influencing these behaviors. This understanding would be particularly beneficial in cultivating employee loyalty, especially among migrant workers from Indonesia. The sample for this study was drawn from major Taiwanese cities, including Taipei, Taichung, Tainan, Kaohsiung, and Chiayi. The research outcomes underscored a substantial impact stemming from both job satisfaction and life satisfaction on OCB. In particular, job satisfaction was found to exhibit a direct and positive correlation with OCB. Furthermore, the duration of employment was positively correlated with both job satisfaction and life satisfaction.